Quality of life in Brazilian martial arts and combat sports practitioners - Schwartz Juliano; Takito Monica; Warburton Darren; Antonietti Leandro; Franchini Emerson (Sciendo, 2021)
Study aim: Martial arts and combat sports have been an alternative for individuals seeking the health benefits of physical activity and exercise, but little is known about its practitioners' quality of life. Therefore, this study aimed to investigate the quality of life of practitioners of five of the most common modalities in Brazil.